The Hidden Curriculum Revisited: A Literature Review on Power, Ideology, and Social Reproduction in Education - Hikmat (Global Writing Academica Researching and Publishing, 2024)
This article revisits the concept of the hidden curriculum by examining its intersections with power, ideology, and social reproduction in education. The hidden curriculum has long been recognized as an implicit mechanism through which values and norms are transmitted beyond formal instruction. In this literature review, previous studies are systematically analyzed to uncover how educational institutions shape and reinforce social hierarchies. The review highlights the role of power relations in defining classroom dynamics and institutional practices. It also explores how ideology operates as a subtle yet pervasive force in legitimizing dominant cultural narratives. Social reproduction emerges as a central outcome, where existing inequalities are sustained through educational structures and practices. By synthesizing diverse theoretical and empirical works, the review provides a comprehensive understanding of the hidden curriculum’s enduring influence. The findings reveal both the persistence of traditional critiques and the emergence of new perspectives that challenge deterministic interpretations. This review contributes by bridging classical insights with contemporary debates, emphasizing the relevance of the hidden curriculum in current educational contexts. The study underscores the importance of critical reflection on how education simultaneously empowers and constrains learners within broader social frameworks.